A critical analysis of the management of craniofacial microsomia - David John David AC (Australasian Journal of Plastic Surgery)
Distraction osteogenesis was introduced into the management of craniofacial microsomia some decades ago. It assumed almost instant popularity without evidence of advantage. Poor long-term results and high rates of relapse prove this technique is unsuitable for all but the most carefully selected patients. While innovation and technological advances are to be celebrated, it is vital that new procedures are rigorously tested against current protocols. It is also imperative, that thorough knowledge of disease pathology and pathogenesis are applied against new procedures. It is the view of the author that many painful, useless operations would be avoided if surgeons better understood these key fundamentals. Furthermore, there must be clear guidelines for the introduction of new techniques and devices, and this must happen independently of manufacturers.